Course of Alternating Hemiplegia of Childhood - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
The natural history and long-term outcome of alternating hemiplegia of childhood (AHC) was studied by questionnaire within a large cohort of 157 patients, as part of the European Network for Research on Alternating Hemiplegia (ENRAH) project.